Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1991
DOI: 10.1115/91-gt-252
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling Research on the Endwall of a Turbine Nozzle Guide Vane in a Short Duration Annular Cascade: Part 1 — Experimental Technique and Results

Abstract: Heat transfer and aerodynamic measurements have been made on the endwalls of an annular cascade of turbine nozzle guide vanes in the presence of film cooling. The results indicate that high levels of cooling effectiveness can be achieved on the endwalls of turbine nozzle guide vanes (NGV). The NGV were operated at the correct engine non-dimensional conditions of Reynolds number, Mach number, gas-to-wall temperature ratio and gas-to-coolant density ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In recent years, there have been many studies in turbine blade film cooling. For example, Abhari and Epstein (1994) studied rotor blade film cooling, Nirmalan and Hylton (1990) reported on linear cascade nozzle guide vane film cooling, Camci and Arts (1985) studied the linear cascade blade film cooling, Harasgama and Burton (1992) presented annual cascade nozzle guide vane end-wall film cooling, Mehendale and Han (1992) studied the modeled blade leading edge film cooling, and Kim et al (1995) reported on the modeled blade tip film cooling. A detailed literature survey in film cooling study can be found in Han and Ekkad (2001), Han et al (2000), and Dunn (2001).…”
Section: Recent Studies On Turbine Blade Film Coolingmentioning
confidence: 99%
“…In recent years, there have been many studies in turbine blade film cooling. For example, Abhari and Epstein (1994) studied rotor blade film cooling, Nirmalan and Hylton (1990) reported on linear cascade nozzle guide vane film cooling, Camci and Arts (1985) studied the linear cascade blade film cooling, Harasgama and Burton (1992) presented annual cascade nozzle guide vane end-wall film cooling, Mehendale and Han (1992) studied the modeled blade leading edge film cooling, and Kim et al (1995) reported on the modeled blade tip film cooling. A detailed literature survey in film cooling study can be found in Han and Ekkad (2001), Han et al (2000), and Dunn (2001).…”
Section: Recent Studies On Turbine Blade Film Coolingmentioning
confidence: 99%
“…Coolant ejection locations have to be viewed with respect to the three-dimensional separation lines on the endwall, taking account of the fact that these can be changed due to upstream endwall coolant ejection. Previous investigations of endwall filmcooling, such as the ones by Blair (1974), Takeishi et al (1989), Granser and Schulenberg (1990), Bourguignon (1985), Bario et al (1989), Harasgama and Burton (1991), Jabbari et al (1994), Goldman and McLallin (1977) and Sieverding and Wilputte (1980) support these conclusions.…”
Section: Introductionmentioning
confidence: 60%
“…Studies of sectored [9] and annular [10] louvers have facilitated a better justified analysis of the change in the structure of the secondary flows and made it possible to estimate the losses when air is released through the end surfaces. Figure 1b is a graph of the loss coefficient ae as a function of the height of the flow-through part behind the sector packet with ë 2ad.avg = 1.12 without release of cooling air on the end surfaces G air.end = 0 and with release of cooling air through apertures on the end surfaces, G air.end = 0.013.…”
Section: Experimental Study Of the Blade Apparatus Of A Stagementioning
confidence: 99%